2007
DOI: 10.1104/pp.107.104000
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Protein Lipoylation Does Not Exclusively Depend on the mtKAS Pathway of de Novo Fatty Acid Synthesis in Arabidopsis

Abstract: The photorespiratory Arabidopsis (Arabidopsis thaliana) mutant gld1 (now designated mtkas-1) is deficient in glycine decarboxylase (GDC) activity, but the exact nature of the genetic defect was not known. We have identified the mtkas-1 locus as gene At2g04540, which encodes b-ketoacyl-[acyl carrier protein (ACP)] synthase (mtKAS), a key enzyme of the mitochondrial fatty acid synthetic system. One of its major products, octanoyl-ACP, is regarded as essential for the intramitochondrial lipoylation of several pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 34 publications
1
66
1
Order By: Relevance
“…Since then, this FAS system has been characterized in yeast and humans (Hiltunen et al, 2010), confirming its multicomponent, type II character. In plant cells, to date only the mtACP isoforms (Shintani and Ohlrogge, 1994;Meyer et al, 2007), mtKAS (Olsen et al, 2004;Yasuno et al, 2004;Ewald et al, 2007), mtPPT (Guan et al, 2015), and mtMCS (Guan and Nikolau, 2016) have been experimentally identified and characterized as components that support mitochondrial fatty acid biosynthesis. In this study, we identified and characterized the Arabidopsis genetic locus AT5G60335 as encoding the mtHD component of the Arabidopsis mtFAS system, which catalyzes the third iterative reaction of the FAS cycle, the dehydration of the 3-hydroxyacyl-ACP intermediate.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since then, this FAS system has been characterized in yeast and humans (Hiltunen et al, 2010), confirming its multicomponent, type II character. In plant cells, to date only the mtACP isoforms (Shintani and Ohlrogge, 1994;Meyer et al, 2007), mtKAS (Olsen et al, 2004;Yasuno et al, 2004;Ewald et al, 2007), mtPPT (Guan et al, 2015), and mtMCS (Guan and Nikolau, 2016) have been experimentally identified and characterized as components that support mitochondrial fatty acid biosynthesis. In this study, we identified and characterized the Arabidopsis genetic locus AT5G60335 as encoding the mtHD component of the Arabidopsis mtFAS system, which catalyzes the third iterative reaction of the FAS cycle, the dehydration of the 3-hydroxyacyl-ACP intermediate.…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic reversal in the elevated CO 2 atmosphere is typical of photorespiratory deficiency (Somerville and Ogren, 1979), with the elevated CO 2 levels inhibiting the oxygenation reaction of Rubisco and, thus, reducing the levels of 2-phosphoglycolate, the starter metabolite of photorespiration. Furthermore, this phenotype also is conferred by mutations in other mtFAS components, such as mtkas (Ewald et al, 2007), mtppt-rnai (Guan et al, 2015), and aae13 (Guan and Nikolau, 2016).…”
Section: Morphological Alterations Associated With Mthd-rnai and Mtkamentioning
confidence: 99%
See 3 more Smart Citations